A lightweight 256 hexadecimal character substitution Cipher algorithm - Ibrahim Lawal; Musa Yusuf; Adamu Sulaiman Usman; Oluwasegun Ishaya Adelaiye (Journal of Electrical Systems and Information Technology)
Abstract Traditionally, playfair matrix encryption is done by encrypting only 8 bits characters to generate ciphers which are equal to the plaintext. Over the years researchers have proposed to incorporate other characters into the plaintext matrix in order to increase the decryption time. However, these solutions have resulted to generating different ciphers and too many ciphertext, thereby increasing the computational resource utilization in terms of memory usage and the size of the ciphertext after encryption. This paper proposes a Hexadecimal Character Substitution Cipher (HCSC) algorithm aimed to reduce the computational resource utilization and reduce the size of the ciphertext after encryption thereby making the proposed algorithm suitable for deployment in mobile devices. The proposed algorithm employs confusion and diffusion to translate a plaintext into Hexadecimal equivalent swap first-order byte of first character with the last-order byte of second character and the last-order byte of the first character with the first byte order of the second character to introduce a modified 16-bit hexadecimal ciphertext. The modified ciphertext is converted into the corresponding 16-bit character representation in order to generate a lightweight ciphertext. The aim of this study was achieved by the following objectives; a design of the HCSC algorithm, an implementation of the proposed HCSC algorithm using python programming language and the evaluation of its performance in comparison with existing study. The result of the comparison showed that the confusion and diffusion introduced in HCSC algorithm has not only increased the decryption time when brute-force technique is used, but also have lower computational resource utilization and lighter in terms of weight when compared to the existing studies based on terms of 8 bits plaintext.